PENGARUH COST INEFFICIENCY, CAPITALIZATION, DIVERSIFICATION, SIZE, DAN, PROFITABILITY TERHADAP LOAN QUALITY - Turnip, Melisa; ., Taswan (Proceeding SENDI_U, 2016)
This study aims about loan quality determinants. Loan quality is determinant which used know health of bank. Bigand small of cost inefficiency and CAR can influance loan quality. The fundamental factors which used in this studycost inefficiency, CAR, diversification, size, and profitability. This study sampled using a pusposive sampling andobtain data of 123 samples. This study is not free from the normality test but free from the classical assumptiontest.These result indicate that cost inefficiency has a negative and significant impact on loan quality. CAR has anegative an significant impact on loan quality. Diversification has a positive and not significant impact on loanquality. Size has a negative and not significant impact on loan quality. Profitability has negative and not significantimpact on loan quality.Key word: Loan quality, cost inefficiency, diversification, size, and profitability